Faktor Yang Berpengaruh Terhadap Pola Asuh Pada Balita - Nafiah, Fitri Kholishatun; Nafisah, Lu'lu; Sistiarani, Colti (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2025)
Health development in Indonesia continues to face significant challenges due to persistent nutritional issues, particularly among children within the first 1,000 days of life. This period is widely recognized as a critical window for meeting optimal nutritional needs to support comprehensive growth and development. A key determinant of a child’s nutritional status is parental caregiving. Proper parenting practices are essential for ensuring children receive a balanced and adequate intake of nutrients tailored to their specific needs. In Demak Regency, the prevalence of underweight, stunting, and wasting remains high. Among all regional health centers, Puskesmas Demak II has recorded the most substantial increase in toddler malnutrition cases, a trend a preliminary study attributed to inadequate parenting practices. This study was designed to systematically investigate the factors influencing parenting practices among caregivers of toddlers at Puskesmas Demak II. Employing a quantitative, cross-sectional design, the research examined a population of 2,233 toddlers. A representative sample of 92 caregivers was selected using a simple random sampling method. Data analysis was conducted through a series of statistical procedures, including univariate, bivariate, and multivariate analyses, to identify significant relationships and predictive factors. The multivariate analysis revealed that three variables independently influenced parenting practices: education (OR=4.394), knowledge (OR=2.953), and attitude (OR=3.282). Of these, education was identified as the most influential variable. These findings underscore the critical need for targeted educational interventions aimed at improving parenting practices. It is therefore recommended that comprehensive education on proper parenting be delivered to key demographic groups, including adolescents, prospective brides, and current parents. Utilizing diverse communication channels such as seminars, workshops, and mass media, these educational initiatives are expected to enhance caregivers' knowledge and skills, thereby facilitating the early prevention of nutritional problems in young children.